The Art of Simile in Ibn Al-Shajari (d. 542 AH) an Operational Study - Kanbar, Fatima Abdel-Jawad; Al-Khaqani, Amal Hussein Hassan (Journal of Ecohumanism, 2024)
This study deals with the art of simile in Ibn Al-Shajari (d. 542 AH) in his printed works, where he presented us with an integrated vision about this rhetorical art. He was creative in defining its meaning and functions, and was interested in defining its pillars and methods of employing it in the literary text, in addition to his treatment of various types of simile. He was also distinguished by his literary taste and critical view in his selection of simile images, which became clear through his rhetorical comments. Thus, his contributions to the art of simile can be considered among the most important rhetorical and critical contributions in the fifth and sixth centuries AH. He is an eloquent encyclopedic scholar who had a wide influence on the rhetoricians who came after him, and the influence of his work continues to this day, as his works were the focus of attention of researchers and scholars.